INTEGRATED AND INNOVATIVE APPROACH TO THE IMPROVEMENT OF PRIMARY CLASS LESSONS - Sultanov , Bakhtiyor Abdumurodovich (Innovative Development in Educational Activities, 2023)
In this article, we discuss the process of integrating physical and spiritual education in the formation of a harmoniously developed generation.